Facial Nerve Arterial Arcade Supply in Dural Arteriovenous Fistulas: Anatomy and Treatment Strategies - Bhatia, K.D.; Kortman, H.; Lee, H.; Waelchli, T.; Radovanovic, I.; Schaafsma, J.D.; Pereira, V.M.; Krings, T. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: Endovascular treatment of petrous dural AVFs may carry a risk of iatrogenic facial nerve palsy if the facial nerve arterial arcade, an anastomotic arterial arch that supplies the geniculate ganglion, is not respected or recognized. Our purpose was to demonstrate that the use of a treatment strategy algorithm incorporating detailed angiographic anatomic assessment allows identification of the facial nerve arterial arcade and therefore safe endovascular treatment.MATERIALS AND METHODS: This was a retrospective cohort study of consecutive petrous dural AVF cases managed at Toronto Western Hospital between 2006 and 2018. Our standard of care consists of detailed angiographic assessment followed by multidisciplinary discussion on management. Arterial supply, primary and secondary treatments undertaken, angiographic outcomes, and clinical outcomes were assessed by 2 independent fellowship-trained interventional neuroradiologists.RESULTS: Fifteen patients had 15 fistulas localized over the petrous temporal bone. Fistulas in all 15 patients had direct cortical venous drainage and received at least partial supply from the facial nerve arterial arcade. Following multidisciplinary evaluation, treatment was performed by endovascular embolization in 8 patients (53%) and microsurgical disconnection in 7 patients (47%). All patients had long-term angiographic cure, and none developed iatrogenic facial nerve palsy.CONCLUSIONS: By means of our treatment strategy based on detailed angiographic assessment and multidisciplinary discussion, approximately half of our patients with petrous AVFs were cured by endovascular treatment, half were cured by an operation, and all had preserved facial nerve function.EVOHethylene-vinyl alcohol copolymerMMAmiddle meningeal arteryTAEtransarterial embolizationTVEtransvenous embolization